The effectiveness of Joint Consultative Committees (JCC) : a case study on Academic Staff Association (PERISAI) in Universiti Malaysia Sabah - Badariah Ab Rahman (2012)
The thesis discusses on indirect employee participation specifically to examine on the practices of Joint Consultative Committee (JCC) through the Academic Staff Association (PERSATUAN STAF AKADEMIK & IKTISAS) or known as PERISAI in Universiti Malaysia Sabah (UMS). The research has three objectives. First, to examine on why and how JCC was formed in UMS. Secondly is to determine the limitation of JCC. The final objective is the evaluation and recommendation on the improvement of JCC (PERISAI). The methodology applied is primarily qualitative where a case study undertaken was using a multi-techniques approach such as structured and semi structured interviews, observation and document analyzing. The major findings of this research can be divided into few sections. First is the lack of information sharing and communication occurs in UMS. Second is lack of trust and confidence towards the relationship between the management-PERISAI academician. Thirdly is the lack of trust and confidence in the leadership of PERISAI. Fourthly, PERISAI has no capacity to influence the decision making process with the management. The findings lead to the reasons for poor commitment among the academician towards PERISAI. The result of the study has some implication to management, PERISAI and academicians in UMS.